2019
DOI: 10.14202/ijoh.2019.9-19
|View full text |Cite
|
Sign up to set email alerts
|

Screening of crows and waterfowls for Salmonella and Listeria monocytogenes infection

Abstract: Background and Aim: Wild birds can carry a number of potential human and animal pathogens. These birds can intrude into human habitats giving the opportunity to transmission of such infection. Therefore, the current study was designed to investigate the role of crows and waterfowls as vectors of Salmonella and Listeria monocytogenes and to compare cultivation methods with direct polymerase chain reaction (PCR) for the detection of infection. Materials and Methods: A total of 200 fecal dropping samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…in wild birds is limited. Jagtap et al [ 212 ] found the isolates gained from wild birds to be susceptible to all antibiotics when subjected to testing, while Fadel et al [ 213 ] were not able to perform AMR testing, as L. monocytogenes isolates lost their viability during preservation. The data currently accessible pertain predominantly to farm-raised poultry.…”
Section: Antimicrobial Resistance Profiles Of Bacteria Isolated From ...mentioning
confidence: 99%
“…in wild birds is limited. Jagtap et al [ 212 ] found the isolates gained from wild birds to be susceptible to all antibiotics when subjected to testing, while Fadel et al [ 213 ] were not able to perform AMR testing, as L. monocytogenes isolates lost their viability during preservation. The data currently accessible pertain predominantly to farm-raised poultry.…”
Section: Antimicrobial Resistance Profiles Of Bacteria Isolated From ...mentioning
confidence: 99%